Digital Transformation in HR: The Impact of HR Analytics on Talent Management and Strategic Decision Making - Siagian, Mei Veronika Sri Endang (YUME : Journal of Management, 2024)
This study investigates the impact of HR analytics and digital transformation on talent management at PT. Adila Prezkifarindo Duta, focusing on how strategic decision-making mediates these relationships. By employing a quantitative research design with random sampling, data was collected from 45 employees, and analyzed using Smart PLS. The findings reveal that both HR analytics and digital transformation significantly influence talent management, with strategic decision-making serving as a crucial intermediary. The direct effects of HR analytics and digital transformation on talent management were found to be positive and significant, while the indirect effects, mediated through strategic decision-making, also demonstrated a notable impact. This research highlights the importance of integrating advanced digital tools and data-driven strategies to optimize talent management practices and improve organizational outcomes. The study provides valuable insights for organizations looking to enhance their HR functions through the adoption of digital transformation and analytics, offering practical recommendations for aligning talent management strategies with broader business goals. Keywords: Talent Management, HR Analytics, Digital Transformation, Strategic Decision Making